SOSIALISASI PEMANFAATAN LIMBAH PEMBAKARAN BATU BARA DALAM PEMBUATAN PAVING BLOK RAMAH LINGKUNGAN - Sumiati Sumiati; Ahmad Syapawi; Revias; Mahmuda; Rizki Prasetya Person (Aptekmas Jurnal Pengabdian pada Masyarakat, 2023)
Precast concrete products are in the form of small concrete blocks, made of fine aggregate, cement and water. Many small business manufacturers of paving blocks have not utilized coal ash waste as an additive and stone ash as fine aggregate. The paving blocks produced are also not standardized, therefore on this occasion we will socialize the results of Kerdosma's research by utilizing coal ash waste in making paving blocks at the Rosida Jaya depot. The aim of this socialization is to apply the results of student research to the community, especially in the manufacture of standardized paving blocks so that they can increase consumer purchasing power, are economical and eco-friendly. The socialization was carried out by discussing the use of coal ash waste as an additive to cement and stone ash as fine aggregate to increase the compressive strength and reduce the absorption of paving blocks. The composition of the research results, printed, tested for compressive strength and absorption so that it can be classified based on SNI 03-0691-1996. Producers and workers  were very enthusiastic and responded to the discussions carried out, where this can be seen in the results of the printed paving block compressive strength when compared to the results of the study which did not differ significantly, but the problem is that the coal ash waste  and stone ash is  very  difficult to obtain, so that if producers use these materials, it will increase production costs.